2023
DOI: 10.4103/jehp.jehp_1696_21
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between personality traits and learning styles in medical education students at Iran University of Medical Sciences: A cross-sectional study

Abstract: BACKGROUND: The relationship between personality traits and learning styles is an attractive subject for researchers. “Learning Style” indicates on a method of education for effective studying. The Kolb's Learning Style is a known theory in the field of learning style. The Kolb's four learning styles include: Divergent, convergent, assimilating, and accommodating. Furthermore, personality, known as relatively fixed and durable characteristics that distinguish people from each other, and personalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…According to the studies carried out by Sohrabi, Sha,ik, and Olsson, they mention that the "accommodative" style is largely found in medical students, in agreement with what was described above. It also mentions that those pigeonholed in this style tend to be concrete and active, in this hemisphere [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…According to the studies carried out by Sohrabi, Sha,ik, and Olsson, they mention that the "accommodative" style is largely found in medical students, in agreement with what was described above. It also mentions that those pigeonholed in this style tend to be concrete and active, in this hemisphere [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, various studies have analyzed other facets regarding the difference in preferred learning style based on student personality. One Iranian study described that Extraverted (E) individuals may be associated with a group-based learning style compared to working alone [34]. Another study in United States dental students found that students with personality types containing Judging (J) prefer well-structured and logical instruction as well as clearly knowing their expectations, among other ndings [35].…”
Section: 3: Academic Performance and Learning Stylesmentioning
confidence: 99%